Root Cause Analysis of Government Readiness in Realizing the Concept of E-Government System: A Case Study of Palu City Government - Permatasari, Ayu; Aknuranda, Ismiarta; Setiawan, Budi Darma (Journal of Information Technology and Computer Science, 2025)
This study aims to analyse the root causes of the readiness issues faced by the Palu City Government in implementing the concept of an E-Government System. The main focus of this research is to assess the government's readiness in realizing the implementation of E-Government System and to identify the root causes of the obstacles encountered in its application in Palu City. The study uses a qualitative approach, with data analysis conducted using the 3x5 Whys method and a Fishbone diagram. The findings indicate that the implementation of the E-Governemnt System in Palu City faces complex challenges, ranging from unaligned regulations, low human resource competencies, limited infrastructure, to suboptimal funding and an organizational culture that is not yet ready for change. Analysis based on academic theories confirms that the success of the E-Governemnt System implementation does not rely solely on technology but also on institutional readiness and human capacity. This research contributes recommendations that can be utilized by the Palu City Government to improve the quality of the E-Government services and achieve the goals of clean, effective, efficient, transparent, and accountable governance. In addition, this study emphasizes the importance of enhancing human resource capacity and managing change in order to optimize the implementation of the E-Government System in Palu City.